Vitamin D as a biomarker in predicting sepsis outcome at a tertiary care hospital - Ghosh, Anirban; Mukhyaprana Prabhu M,; Krishnananda Prabhu,; Changani, Mohit; Patel, Neel; Vijetha Shenoy Belle, (Asian Journal of Medical Sciences, 2023)
Background: Vitamin D has proven immunomodulatory effects. As per the literature, there is a vitamin D deficiency observed in critically ill sepsis patients. Aims and Objectives: The present study was conducted to study the association of vitamin D levels at the time of admission to the intensive care unit (ICU) with mortality and various indices of sepsis assessment like the simplified acute physiology score (SAPS II) along with the age-unadjusted Charlson Comorbidity Index (CCI) and procalcitonin. Materials and Methods: A single centric, observational-longitudinal study was conducted in the ICU with patients of sepsis (n=96). Vitamin D was measured at the time of admission to the ICU. Controls were taken from age- and gender-matched patients without sepsis and with no premorbid illnesses. The objectives of the current study were to assess SAPS II and CCI scores and their predicted mortality amongst various categories of vitamin D levels at the time of admission, to correlate various categories of vitamin D levels with hospital stay and complications or hazards and to assess the sensitivity of vitamin D for prediction of sepsis outcome. Results: The case cohort and controls had average vitamin D levels of 15.33 ng/dL and 41.11 ng/dL, respectively. Patients with vitamin D deficiency had longer hospital and ICU stays and greater rates of morbidity. Observations showed no correlation between vitamin D and serum albumin, WBC count, total cholesterol, triglycerides, LDL, or HDL. The level of vitamin D at the time of admission to the ICU was observed to be highly sensitive (90.6%) to predicting the mortality rates in the ICU due to sepsis. Conclusion: Measurement of vitamin D at the time of admission may be a possible indicator for prediction of sepsis mortality and hospital and ICU length of stay for ICU-admitted patients with sepsis.